Surface Coating of Polyurethane Films with Gelatin, Aspirin and Heparin to Increase the Hemocompatibility of Artificial Vascular Grafts - Simzar Hosseinzadeh; Forough Shams; Roya Fattahi; Ghader Nuoroozi; Elnaz rostami; lida Shahghasempour; Nasim Salehi-Nik; Mahboubeh Bohlouli; Arash Khojasteh; Nazanin Ghasemi; Habibollah Peiravi (Tabriz University of Medical Sciences, 2023)
Purpose: A hemocompatible substrate can offer a wonderful facility for nitric oxide (NO) production by vascular endothelial cells in reaction to the inflammation following injuries. NO inhibits platelet aggregation this is especially critical in small-diameter vessels. Methods: The substrate films were made of polyurethane (PU) in a casting process and after plasma treatments, their surface was chemically decorated with polyethylene glycol (PEG) 2000, gelatin, gelatin-aspirin, gelatin-heparin and gelatin-aspirin-heparin. The concentrations of these ingredients were optimized in order to achieve the biocompatible values and the resulting modifications were characterized by water contact angle and Fourier transform infra-red (FTIR) assays. The values of NO production and platelet adhesion were then examined. Results: The water contact angle of the modified surface was reduced to 26±4⸰ and the newly developed hydrophilic chemical groups were confirmed by FTIR. The respective concentrations of 0.05 mg/ml and 100 mg/mL were found to be the IC50 values for aspirin and heparin. However, after the surface modification with aspirin, the bioactivity of the substrate increased in compared to the other experimental groups. In addition, there was a synergistic effect between these reagents for NO synthesis. While, heparin inhibited platelet adhesion more than aspirin. Conclusion: Because of the highly hydrophilic nature of heparin, this reagent was hydrolyzed faster than aspirin and therefore its influence on platelet aggregation and cell growth was greater. Taken together, the results give the biocompatible concentrations of both biomolecules that are required for endothelial cell proliferation, NO synthesis and platelet adhesion.